-7+x+2x=-31

Simple and best practice solution for -7+x+2x=-31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+x+2x=-31 equation:


Simplifying
-7 + x + 2x = -31

Combine like terms: x + 2x = 3x
-7 + 3x = -31

Solving
-7 + 3x = -31

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3x = -31 + 7

Combine like terms: -7 + 7 = 0
0 + 3x = -31 + 7
3x = -31 + 7

Combine like terms: -31 + 7 = -24
3x = -24

Divide each side by '3'.
x = -8

Simplifying
x = -8

See similar equations:

| 5v^2-11v-1=0 | | X-2/3=4(2/5) | | 6k^2-21k= | | 30e^(t/30)(−ln(2)) | | x-1/3-4=x-9/4 | | Y=4(-3)+4 | | 10+10x=10+10x | | X-2/3=42/5 | | -8x-7=-9x+1 | | 10x+5y-2= | | 0=9x+39x+12 | | 4x+4=-4x-20 | | (1+6i)(1+6i)=0 | | 10/56 | | -[6z-(17z+4)]=4+(10z+1) | | 7t-12=-2+5t | | 2x^2+3=131 | | 8m^2-10=118 | | 4p^2-15p-25= | | 2[t-(2t+11)+10]=2(t+1) | | 3x^2-2x+1=-3x^2+9x+11 | | 0.6k+0.08k=44+8 | | -2p-4(3-3p)=6(p-4)-8 | | 36-4x=5x-9 | | -.333333x+1.33333y=-2.33333 | | x-3/5=5/12 | | 6y-7=-11+4y | | 6k^2+13k+2= | | 7÷7/4 | | -3+12=4 | | -m^2-7m+6=0 | | M^2+7m-6=0 |

Equations solver categories